Influence of Industrially Ceramic Waste Aggregates on Elasticity Properties of Concrete - PETER MANGANJI, DALMON; MOHD. SAM, ABDUL RAHMAN; AWANG, ABDULLAH ZAWAWI; Wan Jusoh, Wan Amizah; Abd Latif, Siti Asma; Loo, Peter (International Journal of Integrated Engineering, 2020)
Deficiency of natural resources leads the construction industry in search of cleaner and greener options for materials in concrete. Thus, utilization of recycled aggregate is an encouraging way to promote sustainability in the production of concrete. However, it is necessary to access their elasticity behaviour for designation of structural concrete. The main objective of this study was to determine the elastic modulus of concrete using recycled ceramic waste aggregates (CWA). In this study, natural fine and coarse aggregates replaced with ceramic waste aggregate in the range of 25%, 50%, and 75%. Fifty-four cubes and twenty-one cylinders were prepared and tested to obtain the physical and mechanical properties of concrete. The aggregates replacement reduces the concrete density but accomplishing the desired compressive strength of concrete. The compressive strength of CWA is equivalent to that of a reference concrete. However, the modulus of elasticity decreased with increased recycled aggregate content. It is possible to adopt ceramic tile waste as recycled aggregate materials as far as considering the stiffness losses in the designing of structural concrete.